Response to teriparatide in Chinese patients with established osteoporosis: osteocalcin and lumbar spine bone-mineral density changes from teriparatide Phase III study - Lu C (Dove Medical Press, 2017)
Chunyan Lu,1 Yun Chen,2 Bin Zhang,2 Yu Chen,2 Fan Bai,2 Decai Chen1 1Department of Endocrinology and Metabolism, West China Hospital, Sichuan University, Chengdu, China; 2Lilly Suzhou Pharmaceutical Co. Ltd, Shanghai, China Abstract: Teriparatide is the first anabolic agent for osteoporosis, and this analysis aimed to understand responses to teriparatide in Chinese patients with established osteoporosis in subgroups. In this Phase III study of teriparatide in China, 362 patients were randomized at a 2:1 ratio to receive subcutaneous teriparatide (20 µg/day) or intranasal salmon calcitonin (200 IU/day) for 24 weeks. Teriparatide treatment produced a significantly greater increase in lumbar spine bone-mineral density (LS-BMD) in postmenopausal women than calcitonin at the 24-week end point. The relationship between osteocalcin (OCN) and LS-BMD was evaluated, and the greatest correlation was found between absolute OCN change at week 12 and percentage change in LS-BMD for patients in the teriparatide group (r=0.24, P<0.001). The correlation weakened at week 24 (r=0.16, P=0.02) and was negligibly negative for calcitonin-treated patients. Proportions of patients achieving >10 µg/L absolute OCN change from baseline in the teriparatide- and calcitonin-treated groups were 81% and 6% at week 12, respectively (P<0.001). Proportions of patients with increased LS-BMD ≥3% at week 24 from baseline were 71% and 35% in the teriparatide- and calcitonin-treated groups, respectively (P<0.001). Proportions of patients meeting both criteria were 63% for the teriparatide group and 1% for the calcitonin-treated group (P<0.001). Subgroup analysis suggested that significant increases in LS-BMD and OCN can be achieved in patients receiving teriparatide, regardless of baseline age, LS-BMD, and fracture times. The rate of treatment-emergent adverse events in each subgroup was similar to the overall analysis. Keywords: osteoporosis, teriparatide, lumbar spine bone-mineral density, osteocalcin